2002
DOI: 10.1115/1.1464871
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compression Testing of Soft Materials

Abstract: Low-strength and low-impedance materials pose significant challenges in the design of experiments to determine dynamic stress-strain responses. When these materials are tested with a conventional split Hopkinson pressure bar, the specimen will not deform homogeneously and the tests are not valid. To obtain valid data, the shape of the incident pulse and the specimen thickness must be designed such that the specimens are in dynamic equilibrium and deform homogeneously at constant strain rates. In addition, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 30 publications
1
99
0
Order By: Relevance
“…For the present purposes we have explored pulse shapers of different materials, for example copper, various polymers and wood, but obtained unsatisfactory results for reaching stress equilibrium when loading forces were smaller than about a hundred Newtons. Chen et al (2002) encountered the same problems but were able to ignore these issues because they were minor perturbations on the larger deformation results that were of interest to them. Through a trial-and-error process we found that employing a composite pulse shaper consisting of a combination of polyurea (1 to 2 mm Fig.…”
Section: Precision Of the Experimental Methods For Linearly Viscoelastmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present purposes we have explored pulse shapers of different materials, for example copper, various polymers and wood, but obtained unsatisfactory results for reaching stress equilibrium when loading forces were smaller than about a hundred Newtons. Chen et al (2002) encountered the same problems but were able to ignore these issues because they were minor perturbations on the larger deformation results that were of interest to them. Through a trial-and-error process we found that employing a composite pulse shaper consisting of a combination of polyurea (1 to 2 mm Fig.…”
Section: Precision Of the Experimental Methods For Linearly Viscoelastmentioning
confidence: 99%
“…The desire or need to deal with a specimen in equilibrium generates a significant challenge that derives from the large impedance mismatch between the specimen and the aluminum bars. To deal with a similar situation involving materials of relatively low rigidity, Chen et al (2002) introduced the pulse shaping technique, which seems to work quite well for polymeric materials under large deformations. For the present purposes we have explored pulse shapers of different materials, for example copper, various polymers and wood, but obtained unsatisfactory results for reaching stress equilibrium when loading forces were smaller than about a hundred Newtons.…”
Section: Precision Of the Experimental Methods For Linearly Viscoelastmentioning
confidence: 99%
“…Materials which have been well-studied in the literature are silicone elastomers [13,66,151], plasticized PVC [152,153] and polyureas [39,40,72,[154][155][156][157][158][159] and polyurethanes [160][161][162]. The rate dependence of these materials depends strongly on the glass transition, and in particular whether this transition affects the room temperature response at strain rates of interest.…”
Section: Rubbery Amorphous Polymersmentioning
confidence: 99%
“…If this is the case, then the force supported by the specimen is equal to both F 1 and F 2 and the stress-strain relationship in the specimen can be calculated using the forces and bar velocities. It is necessary to ensure that polymeric, or other low wave speed specimens, are in equilibrium [66]. This is typically done by comparing the two forces.…”
Section: Dynamic Loading: Split Hopkinson Pressure Barmentioning
confidence: 99%
See 1 more Smart Citation